Correlating structure and electronic band-edge properties in organolead halide perovskites nanoparticles. Issue 22 (18th May 2016) - Zhu, Qiushi; Zheng, Kaibo; Abdellah, Mohamed; Generalov, Alexander; Haase, Dörthe; Carlson, Stefan; Niu, Yuran; Heimdal, Jimmy; Engdahl, Anders; Messing, Maria E.; Pullerits, Tonu; Canton, Sophie E.
Abstract : Lattice strain modifies the subtle stereochemical activity of the Pb 2+ lone-pair in organolead halide perovskites (OHLP) nanoparticles. Abstract : After having emerged as primary contenders in the race for highly efficient optoelectronics materials, organolead halide perovskites (OHLP) are now being investigated in the nanoscale regime as promising building blocks with unique properties. For example, unlike their bulk counterpart, quantum dots of OHLP are brightly luminescent, owing to large exciton binding energies that cannot be rationalized solely on the basis of quantum confinement. Here, we establish the direct correlation between the structure and the electronic band-edge properties of CH3 NH3 PbBr3 nanoparticles. Complementary structural and spectroscopic measurements probing long-range and local order reveal that lattice strain influences the nature of the valence band and modifies the subtle stereochemical activity of the Pb 2+ lone-pair. More generally, this work demonstrates that the stereochemical activity of the lone-pair at the metal site is a specific physicochemical parameter coupled to composition, size and strain, which can be employed to engineer novel functionalities in OHLP nanomaterials.